(untitled) (The Planet, 2024)
Introduction: Lupus nephritis (LN) represents a severe manifestation of systemic lupus erythematosus, and its clinicopathological findings significantly impact the overall disease prognosis. Unfortunately, there is a scarcity of data on lupus nephritis (LN) in Bangladeshi patients in the existing literature. Aim of the study: This study aimed to assess the clinicopathological features and predictors of lupus nephritis patients in Bangladesh. Methods and materials: This cross‑sectional study was conducted at the Department of Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh from January 2023 to July 2023. The study included a total of 30 lupus nephritis patients, selected through purposive sampling. All data were analyzed by using the SPSS version 23.0 program. Results: In this study, the majority of participants (53%) belonged to the ≤24 years age group, with 77% being female. Regarding the classification of lupus nephritis according to the International Society of Nephrology/Renal Pathology Society (ISN/RPS), the majority (53%) fell into class IV. Remarkably, all of our participants (100%) exhibited a SLEDAI 2K score of ≥20. Conclusion: Among the Bangladeshi population, lupus nephritis is more prevalent in younger individuals and females. In the majority of lupus nephritis cases, ISN/RPS score IV is observed, and there is a higher frequency of having a SLEDAI 2K score of ≥20. In addition to the ISN/RPS score, SLEDAI 2K scores can be regarded as another reliable diagnostic tool for evaluating lupus nephritis.